The Role of Green Accounting and Social Disclosure as an Effort to Improve Environmental Performance with ISO 14001 Qualification Standards as Mediation Variables: Study of Mining Companies in Halmahera Regency, North Maluku Province - Risky Soleman; Triadi Agung; Diana Tien (Brilliant International Journal Of Management And Tourism, 2023)
Halmahera Regency, which is in North Maluku Province, currently has a large mining company that can cause environmental pollution. If this happens continuously, the surrounding environment will likely become unhealthy, due to pollution and easy flooding. So that the local government needs to pay attention not to let the condition of this area not be controlled, especially from an environmental safety point of view. This study aims to 1) To examine the effect of green accounting on the environmental performance of mining companies: 2) examine the effect of social disclosure on the environmental performance of mining companies; 3) test the ISO 14001 qualification standard on the environmental performance of mining companies; 4) To test green accounting for environmental performance mediated by ISO 14001 qualification standard variables; 5) To test social disclosure on environmental performance is mediated by ISO 14001 qualification standard variables. This research design uses an explanative quantitative type. The hypothesis in this study was tested using the Partial Least Square (PLS) method. Partial Least Square (PLS) testing is a test method with variance-based Structural Equation Modeling (SEM). This study uses the Smart-PLS 4.0 test tool specifically designed to estimate structural equations based on variance. The results of this study indicate that green accounting has no effect on environmental performance but can be mediated by ISO 14001 qualification standards. In addition, social disclosure affects environmental performance and can be mediated by ISO 14001 qualification standard.